الضبط الإداري في ظل جائحة كورونا - ضيف الله لبنى (جامعة المسيلة, 2021)
يعد الضبط الإداري جملة من الأوامر والنواهي التي تفرضها السلطة وتكون ملزمة للأفراد بهدف تنظيم حرياتهم، إلا أن هذه الأوامر من شانها أن تقيد الحريات العامة للأفراد حفاظا على النظام العام بصوره التقليدية والحديثة، حيث يشكل هذا الأخير الإطار العام الذي تتحرك فيه سلطات الضبط الإداري، وبذلك فحريات الأفراد تمارس في هذا الإطار تفاديا للفوضى التي تؤدي إلى انتكاسها. إلا انه في حالة الظروف الاستثنائية كخطر داهم أو وباء كجائحة كورونا هذه الأخيرة التي أثرت سلبا على حريات الأفراد خاصة فتوسعت صلاحيات سلطات الضبط الإداري المركزية واللامركزية باتخاذ كافة الوسائل اللازمة لمواجهة هذه الظروف. الكلمات المفتاحية:الضبط الإداري، جائحةكورونا، النظامالعام، الأفراد. Abstract: The administrative control is a set of orders and prohibitions that is imposed by the authority and binding on the individuals to regulate their liberties ;however ,these orders would restrict the general liberties to preserve the public regime in both versions traditional and modern ;as the latter constitutes the general framework in which the administrative control authorities move and thus the freedoms of individuals are exercised within this framework in order to avoid the chaos that leads to its setback. However, in the case of exceptional circumstance such as an danger or n epidemic like, corona pandemic ( covid19),which negatively affected the freedoms of individuals in particular ,so the administrative control authorities(central and de centralized ) expanded by taking all necessary measures to confront these circumstances . Keywords: administrative control, corona pandemic and public order (r
Keywords: الضبط الإداري، جائحةكورونا، النظامالعام، الأفراد